Diversidade de ácaros (Acari, Arachnida) em seringueiras (Hevea brasiliensis Muell. Arg., Euphorbiaceae) na região noroeste do Estado de São Paulo, Brasil - Feres, Reinaldo J.F. [UNESP]; Rossa-Feres, Denise de C. [UNESP]; Daud, Rodrigo D. [UNESP]; Santos, Rodrigo S. [UNESP] (Sociedade Brasileira de Zoologia, 2002)
The mites of three rubber tree cultures (Cedral, Pindorama and Taquaritinga) in order to determine the abundance of populations, the richness, the diversity and the degree of similarity among the communities was studied. Twenty one species were found, five of which were common to the three cultures. The richness and the abundance were greatest at the beginning of the dry season. The composition of communities differed probably as consequence of the kind of neighboring vegetation to each area, and because of the acaricid pulverization on the culture of Taquaritinga, reductng the richness of mite species in that area. The influence of neighboring vegetation can be shown by the occurrence of Iphiseiodes zuluagui Denmark & Muma, 1972, a common species to citrus trees, on neighboring rubber trees in Taquaritinga, and Tenuipalpus heveae Baker, 1945, a common species on rubber trees, on a coffee culture neighbor to the rubber trees of Pindorama. This data suggests that mites move among neighbor cultures, and can be an importam factor towards pest management and control. The diversity was small on the three cultures, as a result of the occurrence of one dominam species on each area, Calacarus heveae Feres, 1992 or T. heveae, which are considered pests of the rubber tree. The small diversity and the occurrence of dominant species are patterns expected in monocultures, systems with small environmental heterogeneity.
Mites diversity (Acari, Arachnida) from rubber tree (Hevea brasiliensis Muell. Arg., Euphorbiaceae) in Northwestern of São Paulo State, Brazil
Keywords: Acari; Mites; Hevea brasiliensis; Rubber tree; Biodiversity; Brazil